Goodpasture’s Syndrome and p-ANCA Associated Vasculitis in a Patient of Silicosiderosis: An Unusual Association - Amanjit Bal; Ashim Das; Dheeraj Gupta; Mandeep Garg (Case Reports in Pulmonology)
Introduction. Goodpasture’s syndrome is a rare clinical entity and is characterized by circulating autoantibodies which are principally directed against the glomerular/alveolar basement membrane. The etiology of Goodpasture’s syndrome is still unknown. Lung involvement occurs as a result of lung injury and the exposure of new epitopes to the immune system. Recently, several studies have suggested the role of silica as one of etiological factors in ANCA associated vasculitis and glomerulonephritis. Materials and Methods. We present a case of a 40-year-old welder with silicosiderosis, who developed anti-GBM disease with p-ANCA positivity. Case Report. Patient presented to an emergency with gradually increasing breathlessness along with renal failure and died after short hospital stay. Autopsy pathology findings revealed crescentic glomerulonephritis with linear glomerular basement membrane antibody deposition, splenic vasculitis, pulmonary haemorrhage, and pulmonary silicosiderosis. Conclusion. This case reinforces the role of environmental triggers like exposure to silica, metal dust, and tobacco in pathogenesis of Goodpasture’s syndrome and p-ANCA associated vasculitis.